Hydrometeorological disasters in urban areas of Costa Rica, Central America. (27th May 2021) - Quesada-Román, Adolfo; Villalobos-Portilla, Ernesto; Campos-Durán, Daniela
ABSTRACT: Tropical countries are subjected to natural disasters which cause substantial human and economic losses. Coping with disasters in tropics requires to improve our understanding of the frequency and distribution of hydrometeorological disaster events. These assessments are scarce in many developing countries, despite rapid urban expansion and lacking efficient public policies. Costa Rica's location over the Intertropical Convergence Zone, its mountainous landscapes, and vulnerability generate risks conditions for urbans centers. Here, we analyze the Greater Metropolitan Area of Costa Rica (GAM in Spanish), a region that concentrates 65% of the national population. We analyze the hydrometeorological disasters occurrence and distribution in the GAM as well as a population and social indicators analysis to identify spatial patterns of demographic growth. Our results indicate that 5987 hydrometeorological disasters events were reported in the GAM between 1970 and 2018. From this total, 63.7% were floods, 35.3% landslides, 0.9% droughts and 0.1% storms. Coupling historical natural disasters and public policies to an urban sprawl continuous process in the GAM is a critical tool for land use planning and disaster risk reduction decision makers. Results from this study can enhance our understanding on the spatiotemporal characteristics of natural disasters in developing and/or tropical countries urban areas.